The internally displaced in International law - do they require enhanced protection? - Kiessling, Anja (Department of Public Law, 2014)
This work will examine the situation of the internally displaced from the perspective of international law. Chapter one will provide a brief outline of how the meaning of the term IDP developed and then explain who, in the context of this paper, is covered by the term IDP. Chapter two will then put forth the legal framework applicable to IDPs and examine whether these rules grant sufficient protection. Chapter three will address if and how the international community can enhance their protection. In this context it must be explored whether the principle of state sovereignty still presents a serious challenge to the ability of the international community to intervene on behalf of the internally displaced. Finally, the focus will turn to the situation in the Sudan. It is the country with the largest population of IDPs, estimated at over five million. The example of the Sudan will provide insight into the causes of displacement, the needs of the displaced and whether they receive adequate assistance and protection.